AKULTURASI BUDAYA MAHASISWA DALAM PERGAULAN SOSIAL DI KAMPUS (Studi Kasus Pada Mahasiswa PGSD UPP TEGAL FIP UNNES) - Astuti, Tri (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2017)
The purpose of this study is to analyze the process of acculturation of student culture in social intercourse at campus UPP Tegal UNNES and Analyzing the obstacles faced by students in the process of cultural acculturation in social intercourse at campus UPP Tegal UNNES. The long-term goal is to find strategies or methods of student's cultural adaptation strategy which of course is different from the others. This research uses qualitative approach with case study type. The subjects of the study were all students of PGSD UPP Tegal UNNES. Informants students, lecturers, community Kemandungan and society Debong. Primary data sources are obtained through students because they know exactly about the process of cultural acculturation that takes place on campus. While secondary data sources obtained through reference with the study of cultural acculturation in society. Techniques of collecting data through interviews with informants, observations on campus sera student boarding environment and documentation. The validity of data is done by using source triangulation technique and method. Data were analyzed using Miles and Huberman model which include data collection, data reduction, data presentation and conclusion. Cultural acculturation is a social process that students pass through on campus as they associate with their friends. This process occurs because students have different cultures from each other. The process of meeting the two different cultures, but they are able to co-exist without eliminating the elements of each. They associate with college friends without distinguishing the origin of the region, tribe, religion and race. It can be seen through the activities undertaken on campus, such as student activities, activities in order to meet the tasks of college and so forth. In social intercourse they face obstacles, including language, customs and cultural differences